Highly sensitive electrochemical biosensor for glucose, DNA and protein using gold-polyaniline nanocomposites as a common matrix - Chowdhury, Ankan Dutta; Gangopadhyay, Rupali; De, Amitabha (Sensors and actuators. B, Chemical, 2014)
In this paper, fabrication of a biosensing platform by covalent attachment of biomolecules on PAni nanowire (NW) decorated with gold nanoparticles (AuNP) has been reported. Efficiency of the platform has been evaluated after attachment of three different biomolecules viz. glucose oxidase (GOx), a single stranded DNA (ssDNA) and Lamin A antibody (LAA) for sensing of glucose, complementary DNA strand and Lamin A protein, respectively. Method of immobilization as well as method of detection was somewhat different for different systems. GOx and LAA were attached via NH2 functionalizations on AuNP while thiol-ended ssDNA was directly attached to AuNP surface. Sensing of glucose was monitored via chronoamperometry and the flow cell techniques while DNA detection was carried out via Differential Pulse Voltametry (DPV) and protein detection employing Electrochemical Impedance Spectroscopic (EIS) technique. Fabrication of the electrode was easy, enzymatic activity was well and reproducibility of the sensing process was good enough for sensing of glucose. The lower detection limit (1μM), higher sensitivity (14.63μAmM−1cm−2), greater stability and the excellent specificity indicated excellence of glucose sensor. For DNA sensor, detection of non complementary and complementary strands, even single base mismatch could be well discriminated up to the analyte concentration as low as 1μM. The similar detection limit was also obtained for detection of protein all which proves the suitability of the Au-PAni nanocomposites as a general sensor platform.